Colorful opaque photovoltaic modules with down-converting InP/ZnSexS1-x quantum dot layers. (November 2020) - Jeong, Byeong Guk; Hahm, Donghyo; Park, Jeong Woo; Kim, Jun Young; Song, Hee-Eun; Kang, Min Gu; Jeong, Sohee; Kang, Gihwan; Bae, Wan Ki; Song, Hyung-Jun
Abstract: The luminescent down-shifting (LDS) layer, which transforms incoming high energy solar photons to visible ones, promises augmentation of both photoelectric performance and aesthetic appeals of photovoltaic (PV) modules. For efficient, colored PVs with LDS layer, luminophores with high photoluminescence quantum yield (PL QY), small overlap between absorption and emission spectra, and proven photostability are prerequisites. Here, we demonstrate colorful, opaque PV modules with LDS layers of minimized photon sacrifice enabled by structurally-engineered, eco-friendly InP/ZnSex S1-x quantum dots (QDs). Specifically, composition-controlled, thick shells allow enhanced absorption in the UV region and improved PL QY of QDs. Additionally, the ligand-engineering guarantees the stability of LDS layers after the damp heat test. Benefited from QD-LDS layers, commercially available CIGS and c-Si PV modules are awarded with 40% EQE enhancement in the ultraviolet region and wide-ranging color tunability over the entire visible region by QD-LDS layers. Hence, this integrated approach for desirable luminophores will contribute to the realization of highly-efficient, aesthetically-appealing opaque PV modules. Graphical abstract: Image 1 Highlights: Colorful, opaque PV modules with eco-friendly InP/ZnSeS QDs. Structurally engineered QD with enhanced absorption at UV region and improved PL QYs. Full-colored c-Si PV modules are demonstrated employing core/shell QDs with less than 10% efficiency sacrifice. Ligand engineering enables QDs to withstand at harsh out-door operating conditions.